2009
DOI: 10.1152/ajpheart.00584.2008
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin downregulates SERCA2 gene and protein expression in adult rat ventricular myocytes: regulation by pertussis toxin-sensitive Giprotein and cAMP

Abstract: Hilal-Dandan R, He H, Martin JL, Brunton LL, Dillmann WH. Endothelin downregulates SERCA2 gene and protein expression in adult rat ventricular myocytes: regulation by pertussis toxin-sensitive G i protein and cAMP. Am J Physiol Heart Circ Physiol 296: H728 -H734, 2009. First published January 16, 2009 doi:10.1152/ajpheart.00584.2008.-Downregulation of the sarcoplasmic reticulum calcium ATPase (SERCA2) is associated with diastolic dysfunction in the failing heart. Elevated plasma endothelin-1 (ET) levels are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This study focused on mitochondria, but we now know that the PGC-1␣ transcription cascade and hormones have targets in other organelles as well. Notable in this regard is the recent article by Dillman and coworkers, 13 reporting that ET-1 downregulates mRNA expression and protein levels of the sarcoplasmic reticulum calcium ATPase. Possible impact on sarcomere remodeling must also be determined.…”
Section: What Do We Have To Look Forward To?mentioning
confidence: 99%
“…This study focused on mitochondria, but we now know that the PGC-1␣ transcription cascade and hormones have targets in other organelles as well. Notable in this regard is the recent article by Dillman and coworkers, 13 reporting that ET-1 downregulates mRNA expression and protein levels of the sarcoplasmic reticulum calcium ATPase. Possible impact on sarcomere remodeling must also be determined.…”
Section: What Do We Have To Look Forward To?mentioning
confidence: 99%
“…Interestingly, we found that among genes continuously upregulated at day 1 and 3 post-transplantation in CsA 1 peptide treatment were genes that contribute to the structural integrity of heart muscle fiber such as Nexilin (Nexn, Nelin), (Ohtsuka et al, 1998;Wang et al, 2005;Zhao et al, 2001) and transmembrane ATPases (ATP5b and ATP2a2), (Bers, 2006;Hilal-Dandan et al, 2009;Neckelmann et al, 1989;Seo et al, 2008), (Table 3, and not shown). In addition, among the genes involved in cardiac tissue integrity that were upregulated at 3 days post transplantation were: Myocardin (MYOCD), MYL2, MYH6, and MYH7, (Ching et al, 2005; UI-R-C1-kh-c-05-0-UI.s1 UI-R-C1 Rattus norvegicus cDNA clone UI-R-C1-kh-c-05-0-UI 3, mRNA sequence.…”
Section: Genes Upregulated In Csa 1 Peptide Treatmentmentioning
confidence: 78%
“…These studies also suggest that Nelin regulates the formations of stress fibers, focal adhesion and its signaling complex and may participate in the signal transduction in FAs (focal adhesions) in heart tissue (Wang et al, 2005;Zhao et al, 2001); thus, it is involved in the structure, organization, and integrity of heart tissues. Transmembrane ATPases (ATP5b and ATP2a2) are known to function in energy production and cytoskeletal rearrangements (Bers, 2006;Hilal-Dandan et al, 2009;Neckelmann et al, 1989;Seo et al, 2008). The ATP 2a2 is Ca (21) ATPase intracellular pump that is located in the sacroplasmic reticulum of muscle cells and is involved in regulation of muscle contraction/ relaxation cycle (Bers, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac SERCA2 expression has been shown to be upregulated by increased cellular cAMP levels. 33 Further studies are thus warranted to examine the influence of PDE-III inhibition, for example, with milrinone treatment, on survival and target-organ damage in this particular animal model. Ang II triggers inflammatory response and exerts direct proinflammatory effects in part by blood pressure-independent mechanisms related to activation of the redox-sensitive transcription factors nuclear factor-kB and AP-1, as well as oxidative stress.…”
Section: Discussionmentioning
confidence: 99%